2006
DOI: 10.1016/j.resuscitation.2006.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Training lay-people to use automatic external defibrillators: Are all of their needs being met?

Abstract: This thesis draws upon data gathered during research undertaken with a grant from the Resuscitation Council (UK). It explores the use of Automatic External Defibrillators (AEDs) by laypeople, which is known as Public Access Defibrillation (PAD). Whilst an abundance of research has been undertaken about this phenomenon, it has predominately been conducted using quantitative methods; however the data I am using was collected using a qualitative approach. During the research, fifty-three semi-structured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 169 publications
(310 reference statements)
1
24
0
Order By: Relevance
“…However, there are no clear recommendations on what grade should undergo AED training in schools, and no studies have extensively discussed at what age children should be encouraged to use AEDs in real-life situations [23]. It is also noteworthy that medical experts have previously had the same concerns towards AEDs and have urged caution against allowing AEDs to be used by the general public [39]. It was not until 2000 that the AHA clearly acknowledged the value of AEDs and their safety for lay rescuers [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no clear recommendations on what grade should undergo AED training in schools, and no studies have extensively discussed at what age children should be encouraged to use AEDs in real-life situations [23]. It is also noteworthy that medical experts have previously had the same concerns towards AEDs and have urged caution against allowing AEDs to be used by the general public [39]. It was not until 2000 that the AHA clearly acknowledged the value of AEDs and their safety for lay rescuers [40].…”
Section: Discussionmentioning
confidence: 99%
“…Two participants reported that, following the initial scheme establishment and training, there had been little follow-up by staff of any health-related service and that current first responders had not received ongoing training, leaving them feeling unsupported. Community members felt let down by state authorities and questioned whether volunteering should continue as it might be hindering provision of a statutory service.Harrison-Paul et al (2006) [15]To explore the experiences of lay people who have been trained to use automatic external defibrillators. The research questions were: (1) How can training courses help prepare people for dealing with real life situations?…”
Section: Resultsmentioning
confidence: 99%
“…CFRs felt their role was rewarding, although they expressed a need for praise for the work they did [4] and a concern about the limited opportunities for operational debriefing on their activities [10, 14, 15] CFRs felt they were limited in what they could do because they lacked the skills of paramedic staff. [1, 12] In some instances, this manifested in a concern that they were not doing the right thing [1], while some felt they could and should be able to do more to help patients [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations